As I Remember: Martin C. Martinsen, 1967 - Martin C. Martinsen::::::::: (1967)
Martin C. Martinsen reminiscences about being an early student who later became an instructor. He taught in the Aeronautical Engineering department and was at Cal Poly from 1913-1957.